EVALUATION ENERGY SAVINGS AT MALUKU PROVINCE OFFICE BUILDING IN JAKARTA - Tommy Martin Syauta; Deni Shidqi Khaerudini (Universitas Mercu Buana, 2022)
The electricity is very important to support activities in office building .The equipment like AC ( Air conditioning ) needs more electricity to be operated. The is almost 60% is use to support this system (AC). This percentage describe that air condition system is an equipment that needs more electricity in the office and its become inefficiency in using electricity. To take overcome for this problem we need to efficiency in using energy. One of the method that now used to efficient that energy is called “ energy conversation” This method is using to saving the energy There is one thing that must be done in this activity which is “ energy audit “. Audit energy is one of method calculate IKE ( Intension Consumption Energy) at on the building.The first preliminary audit shown that more energy, which 60% is use to operated the air conditioning (AC) system and 30% to operate lighting system. IKE for the lighting system is still below from maximum standard which is 15 watt/m²The opportunity of saving energy on audit energy in AC system is done by cleaning up consist of : cleaning up filter, propeller corner fin of the evaporator, and the grill of in door unit.